The Influence of Teaching Staff, Curriculum, Work Culture on the Management of Islamic Education - Abd Karim Amarullah; Hapzi Ali; Kasful Anwar (DINASTI RESEARCH, 2023)
This article describes the influence of Islamic education management on educators, curriculum, work culture so that Islamic education management will be very effective in implementation and managerial in an educational institution. The method of writing this literature review article is the research library method, Google Scholar Sourced from online media like Mendeley and others. The results of this article are that 1. Curriculum influences Islamic education management2. Performance influences the management of Islamic education 3. Educational staff influences education management.